Evaluation of quality and biochemical properties of Bovine meat from different rearing systems - Vukašinović, Aleksandra; Fiorani, Federico; Costanzi, Egidia; Cataldi, Samuela; Sorci, Guglielmo; Cencigoga, Beniamino; Albi, Elisabetta (Italian Journal of Food Science, 2025)
The quality of meat plays an important role in maintaining human health. The aim of this study was to characterize the quality traits (color, marbling, and tenderness) of the Longissimus thoracis muscle and to compare the antioxi-dant capacity, phospholipid (PL) composition, and advanced glycation end products (AGEPs) in the diaphragm of beef from organic and traditional farming. Additionally, the effects of short supply chains (SSCs) and long supply chains (LSCs) were compared. For statistical analysis, t-tests and ANOVA were used. The results demonstrated that meat from organically raised animals had 1.7 times higher antioxidant power, richer in PL content by 1.25 and 1.12 times, and cholesterol levels were 3.38 and 2.84 times higher than meat from traditionally raised animals in both SSCs and LSCs, respectively. Conversely, the LSC doubled the value of AGEPs in organic meat.